Correction Of Uterine Torsion In Sirohi Goat By Modified Schaffer’s Method - Hussain, Khalid; Shah, I.A.; Shah, M.A.; Kumar, Suneel; Negi , S.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Uterine torsion is one of the frequent maternal causes of dystocia in dairy animals that commonly occurs near parturition. In small ruminants maternal dystocia due to uterine torsion is occasional and accounts for 2% of etiological factors (Jackson, 2004). The low incidence of uterine torsion in goats might be due to difference in the attachment of mesometrium, i.e. sublumbar rather than subillial attachment (Fazer et al., 1996). The entire length of the pregnant uterine horn rotates on its longitudinal axis to the left (anti-clockwise) or right side (clockwise). The fetus and its membranes also rotate with the uterus; there is compression of the blood supply to the fetus, hemorrhage or seepage of blood in the allantoic cavity and resultant death of the fetus in utero. Since uterine torsion frequently occurs during parturition, the birth canal is occluded because of twisting and delivery of fetus cannot occur. Uterine torsion is a diagnostic dilemma for veterinarians and a difficult obstetrical procedure for less experienced persons. The treatment regimens for the uterine torsion include rolling of dam while giving pressure on flank (Dhaliwal et al., 1986) and caesarian section (Bansod and Srivastava, 1991).